2007
DOI: 10.1007/s00438-007-0295-0
|View full text |Cite
|
Sign up to set email alerts
|

GalEa retrotransposons from galatheid squat lobsters (Decapoda, Anomura) define a new clade of Ty1/copia-like elements restricted to aquatic species

Abstract: Crustacean species have not been examined in great detail for their transposable elements content. Here we focus on galatheid crabs, which are one of the most diverse and widespread taxonomic groups of Decapoda. Ty1/copia retrotransposons are a diverse and taxonomically dispersed group. Using degenerate primers, we isolated several DNA fragments that show homology with Ty1/copia retroelements reverse transcriptase gene. We named the corresponding elements from which they originated GalEa1 to GalEa3 and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…The length of the fungal GalEa retrotransposons ranges from 5428 bp (Oima1 from O. maius ) to 7018 bp (Cogra2 from C. graminicola ), with an average length of 6100 bp. They appear thus larger than the GalEa elements previously described in metazoans (up to 4949 bp for CoRex1 [24]). They are however very similar to the other GalEa with : (i) LTRs bordered by 5’-TGT and 3’-CA with an average size of 235 bp (from 138 to 311 bp, excluding the outlier Cormil element that has 545 bp LTRs); (ii) a 5 bp Target Site Duplication as observed for Zeco1 in D. rerio ; (iii) a large single ORF; and (iv) a great variability in the PolyPurine Tract signal.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The length of the fungal GalEa retrotransposons ranges from 5428 bp (Oima1 from O. maius ) to 7018 bp (Cogra2 from C. graminicola ), with an average length of 6100 bp. They appear thus larger than the GalEa elements previously described in metazoans (up to 4949 bp for CoRex1 [24]). They are however very similar to the other GalEa with : (i) LTRs bordered by 5’-TGT and 3’-CA with an average size of 235 bp (from 138 to 311 bp, excluding the outlier Cormil element that has 545 bp LTRs); (ii) a 5 bp Target Site Duplication as observed for Zeco1 in D. rerio ; (iii) a large single ORF; and (iv) a great variability in the PolyPurine Tract signal.…”
Section: Resultsmentioning
confidence: 61%
“…The branch 2 groups at least 13 widely distributed clades among eukaryotes, while the branch 1 comprises Ty (Pseudovirus) elements found in fungi together with four clades of CoDi-like elements from diatoms and the GalEa clade. Initially described in galatheids (Galatheid Euminida a nnulosa [24]), GalEa elements have been actually more successful among metazoan species than initially thought with some elements identified in Mollusca, Chordata, Cnidaria, Ctenophora, Echinoderma and Hemichordata [15]. Numerous GalEa sequences have been also identified from some microbial metagenomes collected during the Sargasso Sea surveys [25].…”
Section: Introductionmentioning
confidence: 99%
“…At present, however, LTR sequences have not been identified in PyRE10G, whereas most GalEa group elements possess LTR sequences at both ends. Considering the distribution of GalEa elements among phylogenetically distant aquatic animals, Terrat et al (2008) speculated horizontal gene transfer as one reason for the unusual distribution. The present data raise the possibility that GalEa group elements exist in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In the tree, PyRE1G1 was grouped in the clade of usual copia retrotransposons while PyRE10G was in another clade of the GalEa group. Most recently, Terrat et al reported that GalEa elements isolated from galatheid crabs are closely related to copia-like elements in phylogenetically distant animals such as Ciona intestinalis, Oryzias latipes, and Danio rerio and concluded that the GalEa group is a new clade of copia-like retrotransposons in aquatic animals (Terrat et al, 2008). The inclusion of PyRE10G in the clade of GalEa elements (Fig.…”
Section: Pyre1g1 and Pyre10g Occupy Different Clades Among Copia Elemmentioning
confidence: 96%
See 1 more Smart Citation